2003
DOI: 10.1002/neu.10298
|View full text |Cite
|
Sign up to set email alerts
|

Tyramine and octopamine have opposite effects on the locomotion of Drosophila larvae

Abstract: Biogenic amines are believed to play important roles in producing behaviors. Although some biogenic amines have been extensively studied in both vertebrates and invertebrates, little is known about the effects of trace amines like tyramine and octopamine. We investigated how trace amines affect behaviors using quantitative morphometric methods on Drosophila Tbetah(nM18) and iav(N) mutants that have altered levels of tyramine and octopamine. Locomotion of wild-type and mutant third instar larvae was analyzed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
183
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(193 citation statements)
references
References 45 publications
9
183
0
Order By: Relevance
“…In the Drosophila larva, both TA and OA have been proposed to have opposing effects on locomotion, with OA stimulating and TA possibly inhibiting the CPG (Saraswati et al 2004;Fox et al 2006). We do not detect a decrease (or increase) in locomotion when either dVMAT mutant or WT larvae are fed TA.…”
Section: Discussionmentioning
confidence: 99%
“…In the Drosophila larva, both TA and OA have been proposed to have opposing effects on locomotion, with OA stimulating and TA possibly inhibiting the CPG (Saraswati et al 2004;Fox et al 2006). We do not detect a decrease (or increase) in locomotion when either dVMAT mutant or WT larvae are fed TA.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that tyramine and octopamine have antagonistic effects and suggest that behavioral regulation may depend on the balance of these two hormones (7,32). Thus, T␤M may be expected to function under k cat /K m conditions for all three substrates in vivo, making the enzyme exquisitely sensitive to small shifts in cellular conditions.…”
Section: Discussionmentioning
confidence: 99%
“…TA-and OA-specific neurons, receptors, signaling pathways, and phenotypes have been described in both insects (Saudou et al, 1990) and nematodes . In insects, TA and OA have opposite effects on a variety of behaviors, including locomotion, excitatory junction potentials in muscle strips, and chloride ion conductance across Malpighian tubules in Drosophila (Nagaya et al, 2002;Blumenthal, 2003;Saraswati et al, 2003). In general, insect GPCRs with a preference for TA couple to a decrease in cAMP levels, whereas GPCRs with a preference for OA couple to an elevation in cAMP levels (Roeder, 2005).…”
Section: Figurementioning
confidence: 99%